Pitch discrimination with mixtures of three concurrent harmonic complexes - Graves, Jackson E. (J Acoust Soc Am, 2019)
In natural listening contexts, especially in music, it is common to hear three or more simultaneous pitches, but few empirical or theoretical studies have addressed how this is achieved. Place and pattern-recognition theories of pitch require at least some harmonics to be spectrally resolved for pitch to be extracted, but it is unclear how often such conditions exist when multiple complex tones are presented together. In three behavioral experiments, mixtures of three concurrent complexes were filtered into a single bandpass spectral region, and the relationship between the fundamental frequencies and spectral region was varied in order to manipulate the extent to which harmonics were resolved either before or after mixing. In experiment 1, listeners discriminated major from minor triads (a difference of 1 semitone in one note of the triad). In experiments 2 and 3, listeners compared the pitch of a probe tone with that of a subsequent target, embedded within two other tones. All three experiments demonstrated above-chance performance, even in conditions where the combinations of harmonic components were unlikely to be resolved after mixing, suggesting that fully resolved harmonics may not be necessary to extract the pitch from multiple simultaneous complexes.